Pengaruh Pelaksanaan Prenatal Gentle Yoga Terhadap Kecemasan Menjelang Persalinan Pada Ibu Hamil Primigravida Trimester Iii Di Klinik Bidan Kita Klaten - Ritsma Zunira Aryani; Rohmi Handayani; Dewi Susilowati (Jurnal Kebidanan dan Kesehatan Tradisional, 2018)
Abstract Background: Prolonged anxiety at labor may result in abnormal labor and unfavorable effects on the fetus. To break the chain of anxiety can be done with prenatal gentle yoga, because in the prenatal gentle yoga there are pose that can make the pregnant woman relax.To know the characteristics of espondents, to know the average anxietyscore before and after prenatal gentle yoga and to know the impact of prenatal gentle yoga implementation on the anxiety before the delivery of primigravida third trimester pregnant women at Bidan Kita Clinic, Klaten.The research used quasy experiment with one group pretest-posttest approach. Method:The sampling technique used is total sampling, obtained the number of samples of 32 trimester pregnant women III who follow prenatal gentle yoga in the first time. Correlation analysis technique used Paired T Test. From 32 respondents, showed that the majority (97%) of espondents were 2035 years ld with higher education background (50%) and worked as private (37%), the average anxiety score before prenatal gentle yoga was 27.4375 and the average anxiety score after prenatal gentle yoga decreased to 23.1563. The anxiety degradation score ahead of delivery to the respondents was 4.2812. Result: The result of data normality test, distribution of data in this research is normal distribution hence correlation test used Paired T test with value p value is 0.000 (p <0.05). There is a significant decrease in respondents' anxiety scores. Conclusion: There is a strong impact between the prenatal gentle yoga exercise on heanxiety winning of labor in pregnant primigravida in third trimester at Bidan Kita Clinic, Klaten.